The Effect Of Implementing Ball Mastery On Improving Football Dribbling Skills Aged 11-12 Years At SSB Putra Debes Bali - Suprapto, Kennedy Raga Setya; Kusuma, Ketut Chandra Adinata; Ariani, Ni Luh Putu (Universitas Pendidikan Ganesha, 2023)
This research aims to determine the effect of implementing ball mastery on improving soccer dribbling skills aged 11-12 years at SSB Putra Debes Bali. The research design used is experimental research. The sample for this research was 30 SSB Putra Debes Bali students. This research sample was divided into two groups, namely the experimental group with ball mastery training, totaling 15 students, and the control group with ladder drill training, totaling 15 students. The data analysis technique used in this research is the Wilcoxon test, which is used to analyze the differences between pretest and posttest scores in the experimental group and control group. Suggestions that can be given to coaches and students of SSB Putra Debes Bali, it is best to use ball mastery training as a form of training. To improve the results of dribbling training, according to the results of research that has been carried out, it turns out that ball mastery training has a better influence on the results of students' dribbling training at SSB Putra Debes Bali.